HUBUNGAN PENGGUNAAN MEDIA SOSIAL DENGAN PENGETAHUAN REMAJA PUTRI TENTANG RESIKO PERNIKAHAN DINI - Dian Dwi Pratiwi; Franshisca Sihombing, Sarmauli; Fahnawal, T. Marzila (Universitas Batam, 2025)
ABSTRACT Early marriage, also known as young marriage, refers to marriage that occurs when one or both partners are still under the age of 19. Teenage girls who marry at an inappropriate age are at risk of experiencing reproductive health and mental health problems, such as the possibility of experiencing complications during childbirth or the risk of death during childbirth between 35 and 55 percent. Social media is one of the most popular platforms among teenagers, where one of the negative impacts of social media for teenagers is early marriage. For this reason, researchers conducted a study on the relationship between social media use and teenage girls' knowledge of the risks of early marriage.This study is a cross-sectional study, where the study was conducted with the aim of determining the relationship between social media use and adolescent girls' knowledge of the risks of early marriage. The population in this study was 60 adolescent girls at SMAN 1 Kuala Kampar. The data obtained were then analyzed and data presentation was carried out systematically.The results of this study will be processed using univariate and bivariate analysis with the Chi-Square statistical test using a statistical program with a significance level value of α = 0.05. Keywords: Social Media, Young Women, Risk of Early Marriage